Students’ Perception of Using PjBL Method in Learning RELT Subject - Arini Arini; Eka Sustri Harida; Sri Rahmadhani Siregar (English Education : English Journal for Teaching and Learning, 2022)
Project based learning is a method that focusing on students centered by using project as the way of practicing knowledge. RELT subject is a subject learnt about research in English framework. This research aim is to know students’ perception of using project based learning in learning RELT subject. The researched also gain the feedback after using this method. This research using qualitative method. Technique sampling was purposive sampling. The sample was sixth students from sixth semester. Instrument of the research was interview. The data analysis using Miles and Huberman model. Using Project based learning in different level of students also give the difference result. Using PjBL in learning RELT subject was effective. It is because the students were in adult age where they can use their critical thinking. So, even this method still had a weak, but students and lecturer still can gain maximum knowledge and experience. Students also active to give feedback, they didn’t hide the problems, this make lecturer easier to fix the problems.